PREFERENCES AND CONSTRAINTS REGARDING MOVING TO A FINAL RESIDENCE: A CASE STUDY IN HITACHI CITY, JAPAN - M. Kinashi (International Association of Lowland Technology, 2013)
Some researchers have argued that a majority of Japanese have a strong desire to continue living in their current residence. This study hypothesized that some of these individuals, however, may well have a strong desire to change residence when they consider that actual requirements for receiving nursing care in the future. This paper, then, investigates preferences for and constraints on moving to a final residence, given the necessity of nursing care. The data are based on a questionnaire survey conducted among inhabitants of detached houses in suburban Hitachi City which is one of the typical suburban cities in Japan. A McNemar's test and correspondence analysis showed that less than 25% of the inhabitants were relatively certain that they would continue living in their current house in the future, whereas most were likely to change their residence whether they wanted to do or not. Furthermore, the inhabitants faced the necessity of compromising in the selection of their future residence (whether or not this involved a change of residence) due to a sense of being undeserving or out of consideration for their children.